VD_FINDINFO Jug / 2014 / 93 vom 17. Januar 2014 - VD Tribunal cantonal (2014)
NON-LIEU, DÉBAT DU TRIBUNAL, PUBLICITÉ DE LA PROCÉDURE | 110 CPP (CH), 310 CPP (CH), 393 CPP (CH), 61 let. c CPP (CH), 70 al. 2 CPP (CH)